2020
DOI: 10.1002/advs.202000065
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Chemiluminescence Microreactor for Ultrastrong and Long‐Lasting Light Emission

Abstract: A porous metal–organic framework [Ba(H 2 L LOMe 2− )·DMF·H 2 O]·2DMF ( UPC‐2 ) (H 4 L LOMe = 4ʹ,4ʹʹʹ‐(2,3,6,7‐tetramethoxyanthracene‐9,10‐diyl)bis([1,1ʹ‐biphenyl]‐3,5‐dicarbo‐xylic acid N,N‐Dimethylformamide [DMF]), which can act as an excellent chemiluminescence microreactor, is designed and constructed. In the framework of UPC‐2 , the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…For example, Cui et al has reported one long-lasting CL hydrogel and porous HRP/ABEI/Co 2+ -CaCO 3 MPs with slow-diffusion-controlled heterogeneous catalysis. , Sun et ael. prepared a porous metal–organic framework of UPC-2 with a proper diffusion ratio to provide a stable and continuous supply for long-lasting light emission . The reason for lasting emission in this work was the slow diffusion rate on the paper surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Cui et al has reported one long-lasting CL hydrogel and porous HRP/ABEI/Co 2+ -CaCO 3 MPs with slow-diffusion-controlled heterogeneous catalysis. , Sun et ael. prepared a porous metal–organic framework of UPC-2 with a proper diffusion ratio to provide a stable and continuous supply for long-lasting light emission . The reason for lasting emission in this work was the slow diffusion rate on the paper surface.…”
Section: Resultsmentioning
confidence: 99%
“…To solve this problem, the slow-diffusion-controlled heterogeneous reaction was adopted to develop the long-lasting CL emission. The typical examples were from the next work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The triphenylene-encapsulated network structure contained open metal sites, as evidenced by the absence of electron density in the vicinity of the Co 2+ ion (Figure ). Such open sites have many potential uses, such as selective interactions with guest molecules for gas storage/separation and sensing. However, they are typically created by a vacuum treatment of network samples at higher temperatures. , In the case of Co-3TPHAP, coordinatively unsaturated metal sites were created simply by guest encapsulation. To the best of our knowledge, this is the first such example in the field of coordination networks.…”
Section: Resultsmentioning
confidence: 99%
“…An ultrastrong and lasting CL will be observed when the fluorescent molecule goes back to the ground state. Apart from that, an amount of necessary solvents and additives is also used to improve the efficiency of CL. As a kind of crystalline porous material formed by the self-assembly of metal ions and organic ligands, metal–organic frameworks (MOFs) have definite spatial structures and provide a good platform for designing and exploring the rational assembly of functional molecules, which show fascinating applications in adsorption, gas separation, catalysis, and so on. Recently, several anthracene-based MOFs that show good CL performance have been reported. In contrast, research on the CL of pyrene-based MOFs is still quite rare.…”
mentioning
confidence: 99%